Tenth Anniversary Edition of Partecipazione e Conflitto. - Mattoni, Alice; Parks, Louisa; Raffini, Luca (PARTECIPAZIONE E CONFLITTO, 2019)
PARTECIPAZIONE E CONFLITTO [Participation and Conflict] was created in 2008, the first journal in Italy to specialize in work analyzing political and social participation. The journal was to be open to interdisciplinary work, internationally oriented, and founded on rigorous criteria for review. 10 years later in 2018, we believe we have respected that aim. In Italy, PaCo is a touchstone for work on contentious politics, political participation and grassroots mobilization in Europe, and is steadily becoming more and more international. In the introduction to our first issue we described the journal as “an ambitious project born of the need to create an autonomous arena for debate dedicated to the study of the dynamics of transformation of contemporary political systems, with a specific focus on the analysis of participation and the political and social conflicts that characterize this. A journal not only about participation, but about political and social studies that place aspects of participation at their core, in all their intrinsic ambivalences, in their constitutive link to the dynamics of conflict”. We invited research and studies that focused on the transformations of politics and its principal actors: parties, interest groups, trade unions, social movements, associations, sub-cultural and counter-cultural communities, citizens’ committees and other forms of more or less formally organized actors “from below”. We sought work that investigated the processes of democratization and new forms of democratic participation in a participatory vein, but also on the ways in which spaces for collective action were being squeezed, and dynamics of identity closure; on spaces opening up or closing down, on new forms of governance at local, national or supranational level, without forgetting those forms of participation and conflict that challenge, in more or less radical ways, the political, social, economic and cultural foundations of contemporary societies.